Life course of the brain during normal aging and Alzheimer's disease - Finch, Caleb (Henry Stewart Talks, 2016)
Neuropathology of Alzheimer's disease (AD), Normal changes of the aging brain, Genetic influences on AD and normal brain aging, Environmental exposures and the risk of AD, AD drugs and drug trials